Redistribution of Tissue Blood Flow After Stellate Ganglion Block in the Rabbit. Issue 6 (1st October 2009) - Terakawa, Yui; Ichinohe, Tatsuya; Kaneko, Yuzuru
Abstract : Background and Objectives: The goal of this study was to compare tissue blood flow at various sites before and after stellate ganglion block (SGB) and to discuss the redistribution of tissue blood flow after SGB. Methods: We studied 16 male Japanese white rabbits. For SGB, the tip of a 26-gauge needle was placed on the left transverse process of the cervical vertebra, 1 to 2 mm caudal to the cricoid cartilage. Either 0.2 mL of 1% lidocaine (lidocaine group) or normal saline solution (saline group) was injected. In the lidocaine group, data were recorded immediately before SGB and at the time when the maximal change in the common carotid arterial blood flow was observed after SGB. In the saline group, data were recorded immediately before SGB and 3 minutes after SGB. Observed variables were blood pressure, heart rate, common carotid arterial blood flow, tongue mucosal blood flow, mandibular bone marrow blood flow (BBF), masseter muscle blood flow (MBF), quadriceps muscle blood flow, liver blood flow, and renal blood flow. Results: Common carotid arterial blood flow, tongue mucosal blood flow, BBF, and MBF on the block side were increased, whereas BBF and MBF on the nonblock side and quadriceps muscle blood flow, liver blood flow, and renal blood flow were decreased after SGB in the lidocaine group. Conclusions: These results indicate that lower limb and visceral blood flow as well as blood flow on the nonblock side are redistributed to the block side after SGB. Redistribution from peripheral tissue may have a more important role than that of visceral blood flow redistribution after SGB.